1969
DOI: 10.1017/s0022172400041851
|View full text |Cite
|
Sign up to set email alerts
|

A mobile form of the Henderson apparatus

Abstract: SUMMARYA modification of the Henderson apparatus is described which is mobile and which can produce bacterial or viral aerosol in air whose relative humidity can be chosen in the range 20–95 %. The apparatus forms a basic utility for microthread, rotating drum or other aerosol studies.Much help and advice has been given by Messrs. J. F. H. Peel and D. J. Garriock of the Engineering Section M.R.E. throughout the development of this apparatus. The proportioning valve is a modification of one originally used for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0

Year Published

1974
1974
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(69 citation statements)
references
References 8 publications
0
69
0
Order By: Relevance
“…This apparatus was designed to deliver a particle size with a mass median diameter of 2.5 m and a geometric standard deviation of approximately 1.8 (28,29). The aerosol was mixed with conditioned air in the spray tube (30) and delivered to the nose of each animal via a modified veterinary anesthesia mask. Samples of the aerosol were taken using an SKC BioSampler (SKC Ltd., Dorset, United Kingdom) and an aerodynamic particle sizer (TSI Instruments Ltd., Bucks, United Kingdom); these processes were controlled and monitored using the AeroMP management platform (Biaera Technologies LLC, Maryland, USA).…”
Section: Methodsmentioning
confidence: 99%
“…This apparatus was designed to deliver a particle size with a mass median diameter of 2.5 m and a geometric standard deviation of approximately 1.8 (28,29). The aerosol was mixed with conditioned air in the spray tube (30) and delivered to the nose of each animal via a modified veterinary anesthesia mask. Samples of the aerosol were taken using an SKC BioSampler (SKC Ltd., Dorset, United Kingdom) and an aerodynamic particle sizer (TSI Instruments Ltd., Bucks, United Kingdom); these processes were controlled and monitored using the AeroMP management platform (Biaera Technologies LLC, Maryland, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Control experiments showed that Antifoam was not detrimental to either the bacterial culture or the animals. The aerosol was conditioned in a modified Henderson apparatus (Druett, 1969). Sixty-five barrierreared, female, 6-8-week-old BALB/c mice (Charles River Laboratories) were placed in a nose-only exposure chamber and exposed for 10 min to a dynamic aerosol.…”
Section: Methodsmentioning
confidence: 99%
“…Aerosols were generated with a 3-jet Collison nebulizer into a Henderson apparatus, modified to operate over a range of relative humidity values (Druett, 1969), and stored in a 55 1 rotating drum (Goldberg et al 1958). Samples were recovered from aerosols for 1 min, using raised impingers with a flow rate of 10-5 1/min (May & Harper, 1957).…”
Section: Organismsmentioning
confidence: 99%